2003
DOI: 10.1038/sj.ejcn.1601752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early extra fluid and food intake on breast milk consumption and infant nutritional status at 5 months of age in an urban and a rural area of Burkina Faso

Abstract: Objective: To assess the effects of early extra fluid and food intake on breast milk consumption and the effects of food intake on 5-month-old infant nutritional status. Design: Cross-sectional surveys. Infants were selected by random choice. Settings: Urban and rural Burkina Faso. Subjects: A total of 97 urban and 69 rural infants were recruited, but 67 and 51, respectively, completed the surveys. Infant selection criteria were: age (570.5-month old), thriving, breastfed, having Burkinabè parents in study are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
15
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 10 publications
7
15
1
1
Order By: Relevance
“…This finding was in agreement with the report from Central Africa Republic, in which poor growth of children is correlated with old age of children [47]. Studies of other developing countries also claimed that stunting is less common in early infancy as they are on breastfeeding [70], however, because of inappropriate complementary feeding practice and higher nutritional demand, the risk of impaired linear growth increases as the child’s age advances [71]. …”
Section: Discussionsupporting
confidence: 90%
“…This finding was in agreement with the report from Central Africa Republic, in which poor growth of children is correlated with old age of children [47]. Studies of other developing countries also claimed that stunting is less common in early infancy as they are on breastfeeding [70], however, because of inappropriate complementary feeding practice and higher nutritional demand, the risk of impaired linear growth increases as the child’s age advances [71]. …”
Section: Discussionsupporting
confidence: 90%
“…Several investigators [20,19] have reported an increased risk of infant undernutrition resulting from sub-optimal feeding during early infancy (discarding of colostrum, delayed initiation of breast feeding, pre-lacteal feeding and non-exclusive breastfeeding). However, as in our study, other investigators did not replicate these findings [37,31]. In Bangladesh, food secure households were more likely to practice sub-optimal infant feeding at the age of 3-6 months [38] but the prevalence of undernutrition was significantly lower in this group compared to food insecure households [39].…”
Section: Discussioncontrasting
confidence: 75%
“…In the current study, the proportion of women delaying initiation of breastfeeding for more than one hour is comparable to the national figure but the proportion of non-excusive breastfeeding at the age of two months and pre-lacteal feeding practices are relatively low [15,36]. The proportion of infants who were given colostrum in the current study is higher than studies from Burkina Faso [31] and India [19]. One possible explanation for the current negative finding might be a lack of power to detect an effect due to the low prevalence of sub-optimal feeding practices.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Data are quite consistent, demonstrating a displacement effect by formula, animal milk, and solid food (21,22). However, recent studies indicate that PBF liquids do not result in lower breast milk intake (23,24). In our study, the deleterious effects of PBF and MBF were of remarkably similar magnitude in all the analyses that we conducted.…”
Section: Discussionsupporting
confidence: 86%